Chapter Сообщение о мирном договоре со Швецией в царских грамотах петра I (1721) и елизаветы I (1743) и традиции дипломатической переписки с венецианским адресатом - Kardanova, Nataliya (Biblioteca di Studi Slavistici, 2019)
This article explores the diplomatic correspondence sent to the Doge of Venice by Peter I (1721) and by his daughter Empress Elizabeth I (1743), informing him of peace treaties that had recently been concluded between Russia and Sweden. Analyzing these letters in the context of Russia's diplomatic and epistolary relations with Venice in the 17th and 18th centuries, we examine their structure and composition with particular attention to the presence of diplomatic and epistolary formulae to identify evolutionary changes in the diplomatic and epistolary etiquette employed by Peter I and his successors.